(untitled) (Innovative professional education, 2025)
The main factors influencing the mechanism of ensuring energy efficiency in the economy of Ukraine are revealed, which include: energy policy; infrastructure; technologies and technological development; legislative framework; financing and investments; education and public awareness. The regulatory and legal support for energy saving is considered: Laws of Ukraine and the Energy Strategy for the period until 2050. It is noted that the Ministry of Education and Science of Ukraine integrates the topic of energy efficiency into the school curriculum within the framework of the implementation of the «LEARN» project. Further exploration of the study will be aimed at developing a methodology for forming energy efficiency competence of future qualified workers in the construction industry